Perceptions of School Resource Officers: Protectors or Prosecutors? - Almanza, Matthew (Criminal justice review, 2023)
Since the 1990s there has been a significant rise in the number of police officers in schools. There have been growing concerns regarding the effects of school resource officers (SRO) on students’ long-term outcomes and whether or not they are an effective aspect of school safety. Public opinion, especially among key stakeholder groups, impacts policy and practice decisions, and, therefore, there is a need to examine and synthesize the current state of the literature on stakeholder perceptions of SROs. We conducted a systematic review of the literature regarding student, teacher, principal, parent, and SRO perceptions of the role and effectiveness of SROs. The findings across thirty-one publications suggest that key stakeholder groups largely report SROs as a positive presence within schools. Findings are mixed across studies, however, and key differences in perceptions of law enforcement among important school stakeholder populations are discussed.